Book Reviews - Sanguineti, Juan José; Sabuy Sabangu, Paulin; Russo, Francesco (Acta Philosophica, 2016)
Andrea Lavazza, Filosofia della mente, La Scuola, Brescia 2015, pp. 214. (Juan José Sanguineti) Antonio Malo, Essere persona. Un’antropologia dell’identità, Armando, Roma 2013, pp. 400. (Paulin Sabuy Sabangu) Jean-Luc Marion, Sant’Agostino. In luogo di sé, trad. it. di Massimo Loris Zannini, Jaca Book, Milano 2014, pp. 418. (Francesco Russo)